Effects of Pandemic on Special Education Teachers Teaching Hearing Impaired (HI) Students - S. Elivera, Mary Janelle; Barriga, Chrisha; L. Basalo, Drachelle Mae; Contridas, Jannah Marie; Endrina, Grace Lee; Cabanilla, Angelito; Cortes, Venus M. (International Journal of Humanities and Education Development (IJHED), 2022)
The goal of this paper was to determine the effects of pandemic on Special Education teachers teaching the hearing impaired (HI) students. This qualitative-quantitative research was designed to see how the COVID-19 pandemic affected teachers who were educating hearing-impaired students during the mandated school closures in March 2020A three-part standardized and customized questionnaire with open-ended interview questions was given to special education teachers from three selected schools in Cebu Province. Participant responses to the online questionnaire revealed that there is a lack of preparation in online teaching which contributes to their stress. In addition, assessing Hearing Impaired students during distance learning were very hard to establish due to lack of preparation and lack of exposure to online teaching before. Also, the results indicated that teachers find it extremely stressful teaching HI students online during COVID-19. With the findings of this study, school leaders may be able to develop protective factors that help to foster resilience in special education teachers during this time of pandemic. School administrators should facilitate in improving the teaching skills of teachers through assessment of their needs and weaknesses in the delivery of instruction online. This includes giving teachers relevant trainings regarding online tools for assessment and strategies that would help them effectively teach their lessons